A STUDY ON THE USE OF ARTIFICIAL INTELLIGENCE TO BOOST PRODUCTIVITY AND CAREER ADVANCEMENT FOR GIG WORKERS IN THE EDUCATION SECTORS - Shagun Srivastava; Ranjeeta Rahul Prajapati (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the role of Artificial Intelligence (AI) in enhancing productivity and facilitating career advancement for gig workers in the education sector. AI, with its capacity to simulate human intelligence through machine learning, offers significant potential to automate routine educational tasks, improve instructional efficiency, and support personalized professional development. As the gig economy reshapes employment structures, particularly in academia where adjunct faculty and freelance educators are increasingly prevalent, AI tools can serve as transformative assets. The research investigates how AI-driven platforms aid in lesson planning, content delivery, and student assessment, while also providing tailored learning paths and networking opportunities to improve employability and job satisfaction. A mixed-method approach, supported by literature and primary data, reveals that despite challenges such as wage inconsistency and job insecurity, the integration of AI enhances gig worker capabilities and work outcomes. Key findings highlight the importance of ethical and strategic implementation of AI tools to foster sustainable productivity gains, while addressing issues of inclusivity and long-term support. This study contributes to the growing discourse on digital transformation in education by offering actionable insights into how AI can empower the gig workforce, ultimately benefiting educational institutions and learners alike.